The Mexican Revolution: American Influence and Working Class Ideologies - Garcia, Dante Alvin (The Toro Historical Review, 2019)
This paper will look at the Mexican Revolution and analyze the relationship between the working class and the Revolutionary leaders in the Northern states. Generally, the working class resided in the northern states of Mexico due to the massive industrialization in those areas by the United States and other foreign entities. Emphasizing the importance of the working class and its relationship with the United States investors and Mexican Revolutionaries I argue that because of massive American influence in the Northern States the working class supported policies that benefited them such as labor reform, opposing any U.S. Involvement, and having quality accessible education. Thereby, motivating Revolutionary leaders to align their political views with those of the working class to build alliances and consolidate power.